2019
DOI: 10.3390/ijerph16245116
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Air Pollution Exposure to Socioeconomic Status: A Cross-Sectional Study on Environmental Injustice among Pregnant Women in Scania, Sweden

Abstract: Environmental injustice, characterized by lower socioeconomic status (SES) persons being subjected to higher air pollution concentrations, was explored among pregnant women in Scania, Sweden. Understanding if the general reduction of air pollution recorded is enjoyed by all SES groups could illuminate existing inequalities and inform policy development. “Maternal Air Pollution in Southern Sweden”, an epidemiological database, contains data for 48,777 pregnancies in Scanian hospital catchment areas and includes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…However, there is also variation within nations and within urban areas in the consumption patterns that lead to such consequences and in who suffers the burdens thereof. A study conducted in the Skåne region of Sweden, showed how pregnant women of what was referred to as 'low socioeconomic status' were subjected to higher levels of air pollution than women of higher socioeconomic status (Flanagan et al 2019). A similar trend was found in a study across nine European metropolitan areas, where higher levels of air pollution was found in areas described as 'deprived' (Samoli et al 2019).…”
Section: A Pluralistic View On Environmental Justicesupporting
confidence: 54%
“…However, there is also variation within nations and within urban areas in the consumption patterns that lead to such consequences and in who suffers the burdens thereof. A study conducted in the Skåne region of Sweden, showed how pregnant women of what was referred to as 'low socioeconomic status' were subjected to higher levels of air pollution than women of higher socioeconomic status (Flanagan et al 2019). A similar trend was found in a study across nine European metropolitan areas, where higher levels of air pollution was found in areas described as 'deprived' (Samoli et al 2019).…”
Section: A Pluralistic View On Environmental Justicesupporting
confidence: 54%
“…Environmental injustice was found to be present in Adama, as women of lower socioeconomic status had consistently greater odds of being exposed to higher levels of ambient NO 2 and NO x concentrations, using solid fuels that produce high levels of PM 2.5 , and living in areas that lack green space. Moreover, odds were stronger for ambient NO 2 exposure when using a higher exposure concentration cut-off (20 µg/m 3 ), which we have previously used when studying environmental injustice in Sweden (Flanagan et al, 2019), as opposed to Adama's mean (13.7 µg/m 3 ), illustrating lower SES persons' increasing risk of exposure to even higher levels of air pollution. These results are also in line with the few environmental injustice studies conducted in Sub-Saharan Africa.…”
Section: Discussionmentioning
confidence: 80%
“…The resulting modeled mean exposure levels of NO 2 and NO x (13.7 µg/m 3 and 29.9 µg/m 3 , respectively), were used to create the final, dichotomized exposure variable: "low exposure" (below the mean) and "high exposure" (above the mean). Additionally, NO 2 and NO x were dichotomized into emission levels below and above 20 µg/m 3 , which corresponds to the cutoff previously used to study environmental injustice in Sweden (Flanagan et al, 2019).…”
Section: Ambient Air Pollutionmentioning
confidence: 99%
“…This indicates that the group that had a doctoral degree generally worked in environments with relatively lower NP concentrations. Although several studies have shown higher exposure among groups with lower education and sociodemographic level [53][54][55], to our knowledge, there have not been studies comparing different groups among highly educated persons. There were no differences in risk perception between different groups of sex, age, or educational levels.…”
Section: Nanoparticle Concentration and Sbs Symptomsmentioning
confidence: 89%